Innovation in Public Funding for Local Journalism: A Case Study of New Jersey's 2018 Civic Information Bill. Issue 6 (2nd July 2020) - Stonbely, Sarah; Weber, Matthew S.; Satullo, Christopher
Abstract: This article explores an effort to direct state-level public funds toward journalism by using a national policy window combined with an intensive grass-roots effort. We use the lens of Kingdon's policy process model to showcase dynamics that contribute to the media policymaking literature. The process and enactment of New Jersey's 2018 Civic Information Consortium bill are analyzed using a combination of archival research and oral history, highlighting the efforts of policy entrepreneurs and knowledge-brokers, who served as key advocates for the bill's passage. However, they faced strong oppositional political factors that dampened their efforts; specifically, a policy window narrowed by institutional pushback and the tradition of conservative opposition to public funding of media limited the ultimate outcome for the novel initiative. Looking at implications for policymaking and media, the results provide a framework for a new model of public funding for journalism, but the case study also highlights the headwinds facing these types of policy initiatives, at least in the current political climate.